DESENTRALISASI KESEHATAN DAN DAMPAKNYA TERHADAP PROGRAM PEMBERANTASAN PENYAKIT MENULAR - Misnaniarti Misnaniarti; Asmaripa Ainy; Rini Mutahar (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
One important aspect of the impact of decentralization policy on health sectors is that budget allocation is fully authorized by each province. Preventive program of contagious disease is one of program strategy in Indonesian health department to enhance community health status, particularly in order to eliminate contagious diseases in community. Financing is one essential factor; therefore, finding an appropriate policy model of budget allocation is urgent. As a result, budget allocation for each contagious disease is able to be balance. The research design was an observational study with combination of qualitative and quantitative methods. The population is including all health officials in South Sumatera. Data were obtained using a checklist of budget allocation model and deep interview regarding supports and factors that halted in preventive programs of contagious diseases. Univariate and content analysis were utilized. The results indicated that budget proportion of preventive program of contagious diseases in each district/region is various, it depended in program that has priorities over in each region. Furthermore, program financing did not depend on number of diseases’ cases in previous year. Consequently, there were some diseases that were not handled very well due to limited budget from the health officials in each region. It might also be because of limited support from local government that has priorities on free medical treatments that need more budget than prevention activities. In summary, decentralization has not showed positive impacts on implication of communicable diseases preventive program, particularly in budget allocation. We recommend that appropriate budget allocation for this program is urgent needed to decrease numbers of communicable diseases in all district health officials in South Sumatera.